Microrna expression patterns associated with average daily weight gain in kangal akkaraman lambs - Gonca Sonmez; Seref Inal (Eurasian Journal of Veterinary Sciences)
Aim: This study aimed to identify miRNAs expressed in Kangal Akkaraman lambs and to identify miRNAs that may be associated with average daily weight gain (ADWG). Materials and Methods: According to their ADWG, lambs were separated into two groups: those with ADWGs between 270-412 g (mean:323 g) were considered to have high daily gain (HDG) and those with ADWGs below 200 g (mean:125 g) were considered to have low daily gain (LDG). Blood samples were taken, and white blood cells were processed for RNA extraction. Illumina Novaseq was used to prepare and sequence miRNA libraries (LDG and HDG groups). Readings were mapped. Additionally, using DESeq R package (1.8.3), differential expression analysis of two groups was carried out. Based on the RNA-seq data, the two miRNAs with the highest fold increase were selected and their expression levels were tested by quantitative Real-time PCR (RTqPCR) Results: There were identified to be 129 known miRNAs, 134 new miRNAs were predicted, 40 significant differentially expressed miRNAs, of which 12 were up-regulated and 28 down-regulated, were identified (LDG vs HDG). According to RNA-seq results, the two miRNAs with the highest fold change were detected; 0,66 (oar-miR-21) and 0,61 (oar-miR-150). It was determined by RT-qPCR that HDG sheep had 0,63 times lower oar-mir-150 expression, which was not statistically significant, compared to LDG sheep. However, oarmir- 21 was found to be statistically significantly less expressed 0,40 times in the HDG group (p < 0,05). Conclusion: It is thought that the obtained data can contribute to ADWG breeding studies in Kangal Akkaraman sheep.